Analisis Kegiatan Literasi SD Negeri 3 Sungai Besar Kota Banjarbaru: Analysis of Literacy Activities in Public Elementary Echool 3 Sungai Besar Banjarbaru City - Faridah, Siti; Saputra, Ridho Indra; Ramadhani, M. Ihsan (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This study aims to analyze literacy activities at SD Negeri 3 Sungai Besar Banjarbaru that have been implemented for two years. These activities aim to increase students' interest in reading, but challenges remain, such as students' low interest in reading and more interest in playing than reading. To improve reading interest and literacy skills, this study used a qualitative case study approach and involved 15 informants consisting of principals, teachers, and students. Data was collected through observation, interviews, documentation, and questionnaires. The results show that students' interest in reading is improving, although there are still some obstacles. The obstacles include limited time allocation, lack of attention from some parents towards literacy activities, low reading interest, narrow reading rooms, and limited variety of reading materials. The curriculum change from K13 to the Merdeka Curriculum also affected the improvement of students' literacy skills. Based on these results, several solutions are recommended, including increased cooperation between schools and parents, additional facilities such as a more adequate reading room, and the provision of more diverse reading materials. The research conclusion shows an increase in students' interest in reading at SD Negeri 3 Sungai Besar which is monitored through the education report card compiled by the central government as an indicator of literacy and numeracy in schools.